2022
DOI: 10.3390/d14121090
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Lepidoptera Species from the Maltese Islands: New and Additional Records, with an Insight into Endemic Diversity

Abstract: This work presents the first outcomes resulting from a DNA barcode reference library of lepidopteran species from Malta. The library presented here was constructed from the specimens collected between 2015 and 2019 and covers the genetic barcodes of 146 species (ca. 25% of lepidopterous Maltese fauna), including four newly recorded Lepidoptera species from the Maltese islands: Apatema baixerasi, Bostra dipectinialis, Oiketicoides lutea, and Phereoeca praecox. The DNA reference barcode library constructed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
2
0
1
Order By: Relevance
“…Multiple BINs are relatively frequent in Lepidoptera species with higher percentages found in studies with higher number of specimens per species and with larger geographic scope. For example, Huemer et al (2020) and Dincă et al (2021) found that 20% of species of European Gelechiidae and 12.2% species of European butterflies exhibit deep splits, while studies of more limited geographical scope found 6% of species in Bavarian Geometrids ( Hausmann et al 2011 ) or even no deep splits in the case of Maltese islands Vella et al (2022) . The dataset includes 10 shared BINs between taxa possibly in need of taxonomical revision:…”
Section: General Descriptionmentioning
confidence: 99%
“…Multiple BINs are relatively frequent in Lepidoptera species with higher percentages found in studies with higher number of specimens per species and with larger geographic scope. For example, Huemer et al (2020) and Dincă et al (2021) found that 20% of species of European Gelechiidae and 12.2% species of European butterflies exhibit deep splits, while studies of more limited geographical scope found 6% of species in Bavarian Geometrids ( Hausmann et al 2011 ) or even no deep splits in the case of Maltese islands Vella et al (2022) . The dataset includes 10 shared BINs between taxa possibly in need of taxonomical revision:…”
Section: General Descriptionmentioning
confidence: 99%
“…Il s'agit de la première mention française pour Apatema baixerasi, espèce décrite de la province de Valencia en Espagne (Vives Moreno, 2001), observée depuis également en Andalousie, mais aussi en Italie (Sardaigne, Sicile, nord du pays) et à Malte (Vella et al, 2022). La biologie de cette espèce est encore méconnue, comme pour de nombreuses autres espèces du genre Apatema Walsingham, 1900 (Falck et al, 2021).…”
Section: Famille Autostichidae Le Marchand 1947unclassified
“…To address these complexities, the use of standard molecular genetic techniques such as DNA barcoding [10] has become invaluable. Utilizing systems such as BOLD [11], which algorithmically clusters different operational taxonomic units (OTUs) into BIN clusters based on DNA sequences [12], allows for improvements in taxonomic identification, revisions, and biodiversity assessments [13][14][15]. This approach contributes to a more comprehensive understanding of the phylogenetic relationships between different species of Pennella, while assisting in better delimitation of species [5,7,16] at all life stages, allowing for improved knowledge of their complex life history.…”
Section: Introductionmentioning
confidence: 99%